Performance Evaluation of Composite CNT/PE-Modified Asphalt Concrete at Binder, Mixture, and Pavement Levels - Albayati, Amjad H.; Al-Mosawe, Hasan; Maher, Ahmed M.; Al-Ani, Aliaa F.; Moudhafar, Mustafa M. (Salehan Institute of Higher Education, 2025)
Advancing the multi-scale performance of asphalt pavements requires innovative binder modifications that address limitations in rutting resistance, fatigue resistance, and durability across the binder, mixture, and structural levels. This study evaluates the performance of asphalt cement, mixtures, and pavement systems modified with a combination of polyethylene (PE) and carbon nanotubes (CNTs). The binder was modified using 4% PE and varying CNT contents (0.5%, 1%, 1.5%, and 2% by weight of the modified binder). Binder performance was assessed through conventional and rheological tests, including penetration, softening point, viscosity, performance grade (PG) evaluation, and master curve analysis. Mixture-level performance was evaluated using Marshall properties, rutting, resilient modulus, and fatigue tests. Long-term pavement behavior was predicted using VESYS 5W software. The results showed that incorporating 1.0% CNT with 4.0% PE significantly improved binder rheology, increasing the true failure temperature by approximately 10% compared to the reference binder. Complex modulus and phase angle master curves also indicated notable improvements at low frequencies. Mixtures containing 2% CNT demonstrated approximately one-third of the permanent strain observed in the reference mix, while PCNT1.0% exhibited the best fatigue resistance. These findings highlight the significant role of combining plastomeric modifiers (PE) with nanoscale materials (CNTs) in enhancing the performance of asphalt binders and mixtures.